Determinan Kurangnya Penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) - Iriyani, Tri; Hikmawati, Nova; Anggraini, Arie (Jurnal Ilmiah Kesehatan Delima, 2025)
The government's efforts to address the population growth rate in Indonesia are by holding a national family planning program. The most effective family planning method is the Long-Term Contraceptive Method (LCM). The use of LCM in Indonesia is still less popular with Fertile Age Couples (PUS) and tends to decline. This study aims to determine the factors associated with the use of LCM in Sambirampak Lor Village in 2023. The purpose of this study was to analyze whether there was a relationship between age, education, knowledge, family support, the role of health workers and culture with the use of LCM in Sambirampak Lor Village, Kotaanyar District. The research design used was cross-sectional. The results showed that the factors of age, education, knowledge, family support, the role of health workers and culture obtained a p-value <0.05 and 85% were not LCM acceptors. Conclusion, there is a significant relationship between age, education, knowledge, family support, the role of health workers and culture with the use of MKJP in Sambirampak Lor village in 2023.